2008
DOI: 10.1002/bem.20443
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone exposure and spatial memory

Abstract: Radiofrequency (RF) emission during mobile phone use has been suggested to impair cognitive functions, that is, working memory. This study investigated the effects of a 2 1/2 h RF exposure (884 MHz) on spatial memory and learning, using a double-blind repeated measures design. The exposure was designed to mimic that experienced during a real-life mobile phone conversation. The design maximized the exposure to the left hemisphere. The average exposure was peak spatial specific absorption rate (psSAR10g) of 1.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
1
30
0
2
Order By: Relevance
“…Also, evaluations of sleepiness before sleep were collected. Cognitive measures have been reported elsewhere [Wiholm et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Also, evaluations of sleepiness before sleep were collected. Cognitive measures have been reported elsewhere [Wiholm et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Sienkiewicz studied the effect of an electromagnetic field at 900 MHz on spatial learning in rats using an eight-armed radial maze and found that placing the rats in this field for 45 minutes each day for 10 consecutive days had no effects on their memories (20). However, at these frequency bands, cell phone waves affect human memory (21,22) and some of the studies have used water and radial mazes at a frequency of 2 450 MHz (7,8,23). Lai et al (7) studied the effect of 45 minutes of irradiation with 2 450 MHz of electromagnetic waves for 10 days on rats' memory using a 12-armed radial maze and found that the radiation affected memory in the hippocampal region of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies are devoted to depicting the relationship between radio waves and alterations of biological and behavioural functions or their ecological effects (for review, see Cucurachi et al 2013). Although a direct relationship has not been established between radio wave exposure and health problems (Krewski et al 2007;Vanderstraetan and Verschaeve 2008), behavioural and spatial memory disorders in humans (D'Andrea et al 2003;Wiholm et al 2009) and orientation disorders in honeybees and birds (Warnke 2007) have been suspected and a negative effect of radio waves on the in-hive behaviour and homing flight of honeybees has been reported (Harst et al 2006;Kimmel et al 2007). Cell phone radiations were suspected of affecting the reproductive capacity of Drosophila (Panagopoulos et al 2004) and the egg laying rate of the honeybees' queen (Sharma and Kumar 2010) and inducing the worker piping signal in the hive (Favre 2011).…”
Section: Introductionmentioning
confidence: 99%